Adenoviral vectors persist in vivo and maintain activated CD8+ T cells: implications for their use as vaccines. - Tatsis, N; Fitzgerald, J; Reyes-Sandoval, A; Harris-McCoy, K; Hensley, SE; Zhou, D; Lin, S; Bian, A; Xiang, Z; Iparraguirre, A; Lopez-Camacho, C; Wherry, E; et al. (2007)
CD8(+) T cell-numbers rapidly expand and then contract after exposure to their cognate antigen. Here we show that the sustained frequencies of transgene product-specific CD8(+) T cells elicited by replication-defective adenovirus vectors are linked to persistence of low levels of transcriptionally active adenovirus vector genomes at the site of inoculation, in liver, and lymphatic tissues. Continuously produced small amounts of antigen maintain fully active effector CD8(+) T cells, while also allowing for their differentiation into central memory cells. The long-term persistence of adenoviral vectors may be highly advantageous for their use as vaccines against pathogens for which T-cell-mediated protection requires both fully activated T cells for immediate control of virus-infected cells and central memory CD8(+) T cells that, because of their higher proliferative capacity, may be suited best to eliminate cells infected by pathogens that escaped the initial wave of effector T cells.